Ước lượng hàm cầu tiền thực cho Việt Nam: Hàm ý chính sách từ kết quả so sánh được - Phạm Đình, Long; Bùi Quang, Hiển (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
The quantitative analysis of money demand meaningfully specifies money supply growth, contributing to the implementation of effective monetary policy. This study attempts to estimate money demand for Vietnam between December 2003 and December 2014, using vector error correction and cointegration regression models. By considering the determinants of money demand (M1 and M2) in short and long terms, the empirical results verify the roles of real gold price and effective exchange rate, which strongly and significantly affect money demand in the long run. The other determinants, however, only have subtle effects, concerning money demand functions, which suggests that real money demand functions (M1 and M2) cannot be confirmed as being stable during the surveyed period. Some policy implications are thus recommended based on the analytically comparable results.